Microchip in situ electrosynthesis of silver metallic oxide clusters for ultra-FAST detection of galactose in galactosemic newborns' urine samples12. Issue 21 (23rd September 2016) - García-Carmona, Laura; Rojas, Daniel; González, María Cristina; Escarpa, Alberto
Abstract : This work describes for the first time the coupling of microfluidic chips (MC) to electrosynthetized silver metallic oxide clusters (AgMOCs). Abstract : This work describes for the first time the coupling of microfluidic chips (MC) to electrosynthetized silver metallic oxide clusters (AgMOCs). As an early demonstration of this novel approach, the ultrafast detection of galactose in galactosemic newborns' urine samples is proposed. AgMOCs were in situ electrosynthetized on integrated microchip platinum electrodes using a double pulse technique and characterized in full using scanning electronic microscopy (SEM), energy dispersive X-ray spectroscopy (EDX), X-ray photoelectron spectroscopy (XPS) and electrochemical techniques revealing the presence of silver oxides and electrocatalysis towards galactose as a galactosemia biomarker. Galactose detection in galactosemic newborns' urine samples proceeded in less than 30 s, differentiating between ill and healthy urine samples and requiring negligible urine sample consumption. The significance of the newborns' urine samples confirmed the analytical potency of the MC-AgMOCs approach for future implementation of screening for rare disease diagnosis such as galactosemia.